Evolutionary history of two evergreen Rhododendron species as revealed by chromosome-level genome assembly - Wu, Xiaopei; Zhang, Lu; Wang, Xiuyun; Zhang, Rengang; Jin, Guihua; Hu, Yanting; Yang, Hong; Wu, Zhenzhen; Ma, Yongpeng; Zhang, Chengjun; Wang, Jihua (Frontiers in Plant Science, 2023)
Background The genus Rhododendron (Ericaceae), a species-rich and widely distributed genus of woody plants, is distinguished for the beautiful and diverse flowers. Rhododendron delavayi Franch. and Rhododendron irroratum Franch., are highly attractive species widely distributed in south-west China and abundant new varieties have been selected from their genetic resources. Methods We constructed chromosome-scale genome assemblies for Rhododendron delavayi and Rhododendron irroratum. Phylogenetic and whole-genome duplication analyses were performed to elucidate the evolutionary history of Rhododendron. Further, different types of gene duplications were identified and their contributions to gene family expansion were investigated. Finally, comprehensive characterization and evolutionary analysis of R2R3-MYB and NBS-encoding genes were conducted to explore their evolutionary patterns. Results The phylogenetic analysis classified Rhododendron species into two sister clades, ‘rhododendrons’ and ‘azaleas’. Whole-genome duplication (WGD) analysis unveiled only one WGD event that occurred in Rhododendron after the ancestral γ triplication. Gene duplication and gene family expansion analyses suggested that the younger tandem and proximal duplications contributed greatly to the expansion of gene families involved in secondary metabolite biosynthesis and stress response. The candidate R2R3-MYB genes likely regulating anthocyanin biosynthesis and stress tolerance in Rhododendron will facilitate the breeding for ornamental use. NBS-encoding genes had undergone significant expansion and experienced species-specific gain and loss events in Rhododendron plants. Conclusions The reference genomes presented here will provide important genetic resources for molecular breeding and genetic improvement of plants in this economically important Rhododendron genus.